The Association of a Single-Nucleotide Polymorphism in the Nuclear Factor (Erythroid-Derived 2)-Like 2 Gene With Adverse Drug Reactions, Multimorbidity, and Frailty in Older People. (18th May 2019) - Scutt, Greg; Overall, Andrew; Bakrania, Prijay; Krasteva, Eliseveta; Parekh, Nikesh; Ali, Khalid; Davies, J Graham; Rajkumar, Chakravarthi
Abstract: Susceptibility to adverse drug reactions (ADRs), multimorbidity, and frailty are associated with human aging, yet there is wide variation in the severity and age at which individuals are afflicted. Identifying genetic markers of increased risk of this phenotype would help stratify individuals to specialist interventions. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) regulates a cell's response to stressors, including the expression of enzymes involved in drug metabolism. Its expression has been shown to decline in animal aging models. In this study, we tested the hypothesis that Nrf2 gene ( NFE2L2 ) transcription/translation decline in human aging and that single-nucleotide polymorphisms (SNPs) in the NFE2L2 gene are associated with increased ADR risk, multimorbidity, and frailty in older people. Gene expression and protein levels were measured in peripheral blood mononuclear cells donated from healthy patients aged 18–80 years old. NFE2L2 genotypes were determined at three loci in a subpopulation of patients recruited to the PRIME study (a multicenter prospective cohort study that followed older adults for 8 weeks post-discharge to determine ADR). Both NFE2L2 gene and Nrf2 protein expression declined significantly with age in human peripheral blood mononuclear cells. In the PRIME substudy population, the rs35652124 NFE2L2 SNP was associated with increased ADR risk and decreased frailty and multimorbidity scores.